Academic Reading Challenges in Higher Education: Identifying Barriers and Strategic Responses among EFL Students - Jusak Patty; Aldo Hattu; Inggrit O. Tanasale (Poltanesa, 2025)
Academic reading proficiency is a fundamental determinant of success in higher education, particularly for English as a Foreign Language (EFL) students. This study examined the challenges faced by English Education Study Program students at Pattimura University when reading academic articles. Employing a mixed-methods approach with a convergent parallel design, the research integrated quantitative survey data (n=39) with qualitative insights from focus group discussions (n=8) to examine reading difficulties, contributing factors, and strategic responses. Findings revealed a hierarchical pattern of challenges, with linguistic difficulties (M=3.31) representing the most significant barrier, followed by cognitive processing (M=2.99) and strategic processing challenges (M=2.93). Complex sentence structures (M=3.28) emerged as the dominant linguistic challenge, surpassing specialized terminology (M=3.18) and unfamiliar vocabulary (M=3.21). Reader factors (M=3.11), particularly motivational sustainability with longer texts (M=3.21), exerted slightly greater influence than contextual factors (M=2.91). Students employed diverse strategies to navigate these challenges, including pre-reading orientation, vocabulary support mechanisms, and emerging technology-assisted approaches, though collaborative reading remained underutilized. Identifying "strategic inertia"—students' reluctance to experiment with new approaches—represents a novel contribution to understanding reading strategy development in academic contexts. These findings suggest that practical approaches to developing academic reading skills must simultaneously address multiple dimensions, including linguistic features, cognitive processes, strategic approaches, and affective factors.